(3NWHI aj HYV GdMOhOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3Gddge deG cGf GdhLhO dPGJc hGLHkG cGf GdEecGf dPGJ ZjQc VQHI adeG ESJZfJ Yf GdeGgjg PGJc s
(3BNQgG (B:s
(3NUhUkG OYhGg Cf GdSMQ djS NGQbkG ddYGOI hbO bOefG eG jQTOc Edi GdUhGH Cf aJM GdhgGH fbdJ gPg GdaGFOI GdLdjdI hGdeSCdI GdLejdI ef TQM GdLhgQI GdLdjdI ddbGfi GdeGdci QMeg Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs